Pengaruh Intellectual Capital, Growth Opportunity dan Cash Holding Terhadap Nilai Perusahaan - Leny Suzan; Mentari Utami Supriyadiputri (Jurnal Akademi Akuntansi, 2023)
Purpose: Firm value is a shareholder perception resulting from the company’s performance during the course of business. One of the impressions resulting from the worth of the firm is the value of the stock price. In line with the phenomenon raised regarding the share prices of Indonesia pulp and paper companies listed on Indonesia Stock Excharge and pulp and paper companies in Asia, this is certainly a phenomenon that is used a study. The purpose of this study is to ascertain how Intellectual Capital, Growth Opportunity, and Cash Holding have simultaneous and partial effects on Firm Value.